Framework for Preserving Financial Stability in Montenegro - Radoje Žugić; Nikola Fabris (Journal of Central Banking Theory and Practice, 2014)
The global financial crisis has challenged the traditional monetary policy framework of one instrument (short-term interest rates) – one objective (price stability). More and more central banks nowadays consider financial stability as a monetary policy objective, whereas the Central Bank of Montenegro is the only one that has identified financial stability as its primary objective. As this is a relatively new objective, all central banks endeavouring to attain this objective have been facing numerous difficulties. Therefore, the article analyzes some of these difficulties such as defining financial (in)stability, the selection of indicators, macroeconomic environment for preserving financial stability, and the like. The main objective of the paper is to analyse the framework for preserving financial stability in Montenegro and the challenges that the Central Bank of Montenegro has been facing in accomplishing this objective.
Keywords: E52; E58; 330; Financial stability; Preserving; Montenegro; Central Bank of Montenegro